GAYA BAHASA DALAM SYAIR ‘ṢAWT ṢAFĪR AL-BULBUL’ KARYA AL-AṢMAʿĪ (KAJIAN STILISTIKA) - Hanifah Annisa Salsabila; Rohanda; Nurlinah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aims to reveal how figurative language is used in the poem Ṣawt Ṣafīr al-Bulbul by al-Aṣmaʿī. It is a qualitative research using a descriptive-analytical method. The approach employed in this research is the five-level stylistic analysis theory proposed by Syihabudin Qolyubi. The results of the study show that the poem contains various stylistic features based on the levels of stylistic analysis, namely: (1) Phonological level (Muḥtawiyāt al-ṣawtī): the presence of sound repetition such as ṭab-ṭab, kaʿkʿaʿ, and other rhythmic sounds that create musicality; (2) Morphological level (Muḥtawiyāt al-ṣarfī): forms such as muharwiliy and waylī which are rich in emotional expression; (3) Syntactic level (Muḥtawiyāt al-naḥwī): the use of verbal sentences (jumlah fiʿliyyah) and inversion that contribute to expressive dynamics; (4) Semantic level (Muḥtawiyāt al-dalālī): the use of majāz (metaphor), kināyah (metonymy), and symbolism to convey themes of love and irony; and (5) Imagery level (Muḥtawiyāt al-taṣwīrī): the use of tashbīh (simile), istiʿārah (metaphor), and onomatopoeia to build vivid visual, auditory, and emotional atmospheres. This study demonstrates that al-Aṣmaʿī’s poem combines the power of language and rhythm in a form that is both aesthetic and rich in symbolism.